A 63-Year-Old Male with AIDS and Diffuse Violaceous Plaques - Travis A. Benson; Patrick M. Mulvaney; Mai P. Hoang; Daniela Kroshinsky (MDPI AG, 2019)
Hyperkeratotic Kaposi's sarcoma (KS) is a rare clinicopathologic variant of AIDS-related KS that typically presents with chronic lymphedema and diffuse hyperkeratotic plaques of the lower extremities. Histopathologically, this variant is defined by epidermal hyperplasia, thickened lymphatic walls, and increased numbers of dermal fibroblasts and vascular spaces. Herein, we report the case of a 63-year-old HIV-positive male who presented with this rare hyperkeratotic variant of AIDS-related KS.